Tasks of Mathematics Teaching JDPU (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, special methods of teaching mathematics in elementary grades and the tasks of teaching mathematics aimed at increasing the skills of conscious calculation in performing actions are presented.